Subsonic Aeroelastic Analysis of a Thin Flat Plate - Abang Haji Abdul Majid, Dayang Laila (2001)
The interaction between an aircraft structure and the airflow surrounding it has been known to severely affect the stability, performance and manoeuvrability of the aircraft. These interactions form the heart of aero elasticity, a field that comprises all types of aeroelastic phenomena. In this work, a parametric aeroelastic analysis of a thin flat plate clamped at the leading edge and exposed to subsonic airflow was conducted. The aeroelastic effects predicted to occur was flutter, a type of self-excited oscillation. The analysis was simulated using ZAERO, a panel code aeroelastic program, which requires free vibration input, obtained using MSC-NASTRAN, a finite element code. The flutter equation was obtained using Newton's Law of Motion to model the plate while the airflow was modeled using the Small Disturbance Unsteady Aerodynamic Theory. Free vibration results and flutter results obtained were validated against published works found in reference [8, 60 and 61]. The important parameters studied were the aspect ratio and the mass -ratio of the plate. The effect of the number of free vibration modes employed in the analysis was also tested. From the results, it was shown that the flutter velocity decreased as the mass ratio and aspect ratio were increased. The flutter frequency also decreased with higher mass ratio and at large aspect ratio. The use of a higher number of modes in the flutter analysis was found to increase the accuracy of the flutter.